Judicial Governance and Governing through Courts - Zirk-Sadowski, Marek (Journal of Public Governance)
Courts are administered where a certain part of their activity is concerned. Although the process of arriving at judgments is the main assignment given to courts, judicial administration serves to protect efficiency of judging. At the same time, the problem of administration cannot be resolved by the problem of governance. The problem of good administration is here taken to refer to the internal organization involving judicial officials and judicial office administration. Good governance refers to the exercising of power by the judiciary, where this is understood as a community or organization of judges.The boundary which “court administration” cannot cross relates to the judgment itself and the activities of the person of the judge or judges connected with it, who cannot be regulated in an administrative way, but only by means of powers assigned to self-governing authorities of the judiciary.From a political point of view, there are no bases for applying EU rules of good administration (personified in The European Code of Good Administration) to judicial administration, and in fact such an effort would only be possible in regard to some dimensions of the judicial administration (e.g. where access to information concerning the activities of the court is concerned).This work goes on to focus in particular on the other problem described, i.e. the relation between judicial governance and the EU category of good governance.A question concerning the indispensable features of judicial governance was posed, as was one on whether the category of good governance can be taken to relate to judicial power. It emerges that, once account has been taken of the above deliberations, the answers to the questions are ultimately found to depend on the theoretical and philosophical concepts underpinning the activity of judging itself.